Tintinnids (Ciliophora, Oligotrichea) within power plant discharge and marine protected areas in Masinloc-Oyon Bay - Jane Abigail Santiago; Ma Carmen Ablan-Lagman (Check List, 2021)
There are only five studies on tintinnids of the Philippines. We present a checklist of tintinnids (Ciliophora, Oligotrichea) from Masinloc-Oyon Bay, Province of Zambales, West Philippine Sea. Masinloc-Oyon Bay is a unique in having both marine protected areas and a coal-fired thermal power plant within the same bay. Field sampling was performed in July 2017, which recorded 10 species belonging to one order, six families, and seven genera. Station 1 inside the power plant’s outfall had the lowest diversity, whereas the stations within marine protected areas had a relatively higher species diversity index. Our new data are the first records of tintinnid species in Masinloc-Oyon Bay. These records add to the regional checklist of the Philippine Sea.